Tantangan dan Strategi Pengembangan Perguruan Pencak Silat di Kota Tangerang Selatan - Salam, Fitrah Febri; Suwandi; Alfi, Nurfauzan; Rosyid, Nurfaizal; Aribowo, Pinkan Claudia (CV. Kurnia Grup, 2024)
This study aims to identify and analyze the challenges faced by pencak silat colleges in South Tangerang City, specifically related to limited training facilities and lack of educational support. Using quantitative methods, data was obtained through a survey involving 34 pencak silat colleges in the region. The survey consisted of several indicators including the availability of facilities, government support, integration of pencak silat in formal education, and the frequency of competitions attended by students. The results of the analysis showed that 78% of the perguruan experienced significant limitations in training facilities, with an average score of 4.2 out of a scale of 5. 65% of respondents also revealed a lack of government support in the form of facilities and infrastructure assistance, which was reflected in the average score of 3.8. In addition, 71% of colleges rated the importance of increasing the time and quality of pencak silat lessons in schools, with an average score of 4.1. The results of this study suggest increased government support in the provision of facilities as well as the integration of pencak silat in the physical education curriculum in schools. Thus, pencak silat in South Tangerang City is expected to develop more optimally and sustainably as part of Indonesia's cultural heritage.